2019
DOI: 10.1155/2019/9089035
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Extract of Black Sticky Rice and Dill Improves Poststroke Cognitive Impairment in Metabolic Syndrome Condition

Abstract: Despite the increase in cognitive deficit following stroke in metabolic syndrome (MetS) condition, the therapeutic strategy is still limited. Since oxidative stress and neuroinflammation play the crucial roles on the pathophysiology of aforementioned conditions, the cognitive enhancing effect of the combined extract of Oryza sativa and Anethum graveolens was considered based on their antioxidant, anti-inflammation, and neuroprotective effects together with the synergistic effect concept. Male Wistar rats weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…Rice extract and the purified compounds from rice have been reported to act as biological agents for improved human health, especially coloured rice 7,8 . The extract of black sticky rice ( Oryza sativa L) combined with dill has improved poststroke cognitive impairment in metabolic syndrome condition 9 . Lee et al 10 showed that the purified compound from black rice ( O sativa L) had the inhibitory activity on breast cancer cell proliferation and hyperglycaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Rice extract and the purified compounds from rice have been reported to act as biological agents for improved human health, especially coloured rice 7,8 . The extract of black sticky rice ( Oryza sativa L) combined with dill has improved poststroke cognitive impairment in metabolic syndrome condition 9 . Lee et al 10 showed that the purified compound from black rice ( O sativa L) had the inhibitory activity on breast cancer cell proliferation and hyperglycaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that the substance possessing antioxidant and anti-inflammation such as the combined extract of black stick rice and dill significantly improves brain damage and deficits in an animal model of ischemic stroke in MetS condition [10,11]. Our previous study also clearly demonstrates that the phytosome containing the combined extract of ginger rhizome and mulberry fruit (PMG) can also decrease oxidative stress and inflammation [12].…”
Section: Introductionmentioning
confidence: 81%
“…The underlying mechanism of memory impairment in MetS appears to be associated with the reduction of many factors including the function of the cholinergic system and signal transduction via the ERK pathway together with the reduction of neuron density in the hippocampus [6]. Recently, it has been demonstrated that stroke in MetS can also induce memory impairment [7]. The underlying pathophysiology of the aforementioned condition is also associated with a reduction of the cholinergic system and neuron density in the hippocampus but with an increase in oxidative stress and inflammation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that stroke in MetS can also induce memory impairment [7]. The underlying pathophysiology of the aforementioned condition is also associated with a reduction of the cholinergic system and neuron density in the hippocampus but with an increase in oxidative stress and inflammation [7]. Since memory impairments in both MetS and MetS with stroke are associated with inflammation and the reduction of neuron density, the cognitive enhancing effect of substances possessing anti-inflammatory and neuroprotective effects have gained attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation